Laboratory diagnosis of H. pylori among dyspeptic patients using Culture and Rapid urease test - Mohammed Shukri Saadi, Hogir; Yahya Saeed, Ali (Kurdistan Journal of Applied Research, 2019)
Globally Helicobacter pylori has been defined is the prime reason of stomach ulcer and gastric cancer. Medical laboratory analysis of H. pylori infection is done by two ways invasive and non- invasive methods. Invasive techniques frequently disapproved by patients because it is inconvenient but still remain reliable methods. Among invasive methods, culture is considered as gold standard method from which other methods are compared. A sum of eighty six persons with average of ages between 18-77 years old with mean 37.58 years ± (forty three males , forty three females) who visited to endoscopic center / Azadi Teaching Hospital for endoscopic examination from June to Oct. 2013.From everyone , two antral biopsies, one for urease test, the other for culture were collected. Biographies from each case were taken in a questionnaire form after approval by Research Ethics Committee of the college of medicine / Duhok university. H. pylorus was found in 37.2% and 68% by Culture and Rapid urease test respectively. The biggest value percentage of H. pylori positive cases was detected by rapid urease test while the fewest value percentage was by Culture. Combination of both tests it did not approve as a diagnostic test for detection of this pathogenic bacteria. The study did not detect any statistical correlation on the impact of age factor on H. pylori infection by both methods. In this research appear males were less positive for H. pylori than females by urease test and no such statistical association was noticed count on the sex and Helicobacter pylori pathogenicity via culture. Research never noticed any considerable correlation was found between smoking status and patient's residence with H. pylori positive cases by both methods. This study was performed to estimate the appropriate and better diagnostic tests for diagnosis of H. pylori among various types of samples. Due to the increasing incidence of treatment failure (caused in part by antibiotic resistance), post-treatment testing is recommended to confirm H. pylori eradication. Knowledge of the epidemic and the Routes of transmission of this pathogen are important points to avoid from spreading and may be useful in identifying high-risk populations, especially in areas that have high rates of gastric lymphoma, gastric cancer, and gastric ulcer. The current study concludes (RUT) was superlative than culture for the detection of Helicobacter pylori.